Homolog-selective degradation as a strategy to probe the function of CDK6 in AML - Brand, Matthias (Cell Chem Biol, 2018)
The design of selective small-molecules is often stymied by similar ligand binding pockets. Here, we report BSJ-03–123, a phthalimide-based degrader that exploits protein-interface determinants to achieve proteome-wide selectivity for the degradation of cyclin-dependent kinase 6 (CDK6). Pharmacologic CDK6 degradation targets a selective dependency of acute myeloid leukemia cells, and transcriptomics and phosphoproteomics profiling of acute degradation of CDK6 enabled dynamic mapping of its immediate role in coordinating signaling and transcription.